Providing quality pre-primary and primary education in Nigeria in the best interesting of the child (2014)
The major and primary function of all schools is to create and maintain a culture of teaching and learning that is able to develop children's personality, talents, mental and physical abilities to their fullest potential. In this regard, individual, communal, societal and national development cannot be separated from the quality of basic education which a child receives. In other to realize this basic right, a school has to be a place conducive to harmonious and coordinated education capable of offering high quality programmes. Since the school is a place to realize the rights of children to basic education, this paper therefore discusses quality issues in pre-primary and primary education in Nigeria. It enumerates factors that hinder quality education in both levels of education and what could be done to achieve the desired quality.